Some Aspects Regarding Budget Revenues and Expenditure Achieved in Some European Union Countries in Times of Crisis (Financial; Pandemic) - Florina POPA (Communications of International Proceedings, 2023)
The study follows some aspects generated by the manifestation, at the beginning of the current century, of the two types of crises – the financial crisis of 2008 and the pandemic crisis of 2020. Both events, although had different origins and forms of propagation, globally, generated imbalances with severe repercussions on economic and social activities and impact on macroeconomic indicators. The motive behind the study is to signal the impact of the two crises on the evolution of budget revenues and expenditures recorded by the Member States of the European Union, with examples on some representative countries. Elements from the study of reports and recommendations made by competent forums, for some of the Member States, in relation to the observation of some events that determined the way of evolution of the indicators, over a period of time, were followed. Some measures and policies undertaken by the governments of the analysed countries,  for remediate the identified problems, were presented. The intention of originality of the paper results from the chosen theme and the issues signaled over a determined interval of time. The research methodology approached was the documentation from the specialty literature, for formulate ideas and interpretate in the author’s own vision, as well as the analysis of statistical data referring to budget revenues and expenditures and the study of reports and recommendations, made by competent forums, to some of the Member States. The findings signal both the vulnerability of countries’ economies, generated by the negative effects of crises and the potential for recovery, in the two crises.
Keywords: financial crisis; pandemic crisis; comparative aspects; budget revenues and expenditures.